2016
DOI: 10.1080/10245332.2016.1180097
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function in adult ITP patients can be either increased or decreased, compared to healthy controls, and is associated with bleeding risk

Abstract: Objectives: To test whether, together with platelet count, platelet activity could be an important predictor of bleeding risk in immune thrombocytopenia (ITP) patients.Methods: Platelet activity was tested by flow cytometric measurement of agonist induced P-selectin expression and compared between 23 adult ITP patients and 22 healthy volunteers. Results: Platelet activity could be either increased or decreased in ITP patients, compared to healthy volunteers. In the lowest platelet count category, normal to low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…It is reasonable that patients suffering from active bleeding have lower levels of thrombocytes, and functionally different thrombocytes, than patients without bleeding. This inference is supported by a recent study of cITP patients indicating that prediction of bleeding events could be improved by measuring platelet reactivity, particularly in patients with low platelet counts . Our analyses showed that low platelet count was a strong risk factor for bleeding, however; even patients with moderate and mild thrombocytopenia could experience a bleeding event.…”
Section: Discussionsupporting
confidence: 84%
“…It is reasonable that patients suffering from active bleeding have lower levels of thrombocytes, and functionally different thrombocytes, than patients without bleeding. This inference is supported by a recent study of cITP patients indicating that prediction of bleeding events could be improved by measuring platelet reactivity, particularly in patients with low platelet counts . Our analyses showed that low platelet count was a strong risk factor for bleeding, however; even patients with moderate and mild thrombocytopenia could experience a bleeding event.…”
Section: Discussionsupporting
confidence: 84%
“…19 Moreover, they can inhibit megakaryocyte proliferation and differentiation resulting in diminished platelet production. 24 The majority of antiplatelet antibodies is directed against GPIIb/IIIa and GPIb/IX, 25,26 but additional targets have been identified. 24 The majority of antiplatelet antibodies is directed against GPIIb/IIIa and GPIb/IX, 25,26 but additional targets have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Recently, it has been reported that some anti-GP antibodies interfere with platelet functionality, inhibiting platelet aggregation 23 and blood clot formation. 24 The majority of antiplatelet antibodies is directed against GPIIb/IIIa and GPIb/IX, 25,26 but additional targets have been identified. 14 The central role of autoantibodies in the pathogenesis is further illustrated by occurrence of ITP in infants born to mothers with ITP, due to placental transfer of autoantibodies, 27 and by historical use of IgG-depleting treatments like immunoadsorption and plasmapheresis, which lead to a reduction of platelet-associated autoantibodies 28 and increased platelet count.…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic thrombocytopenic purpura (ITP) is an acquired immune‐mediated disease defined as a transient or persistent decrease of platelet count . The decreased platelet count in ITP is associated with an increased rate of bleeding, hemorrhage‐related outcomes and abnormal platelet activity . The global incidence rate for ITP in adults is estimated to be 1.6–3.9/100 000 persons with incidence rates estimated at 5.6–20/100 000 population .…”
Section: Introductionmentioning
confidence: 99%